2012
DOI: 10.1371/journal.pone.0031182
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Cortex Based Sex Differences in Tinnitus Perception: Same Tinnitus Intensity, Same Tinnitus Distress, Different Mood

Abstract: BackgroundTinnitus refers to auditory phantom sensation. It is estimated that for 2% of the population this auditory phantom percept severely affects the quality of life, due to tinnitus related distress. Although the overall distress levels do not differ between sexes in tinnitus, females are more influenced by distress than males. Typically, pain, sleep, and depression are perceived as significantly more severe by female tinnitus patients. Studies on gender differences in emotional regulation indicate that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 75 publications
4
51
0
1
Order By: Relevance
“…This finding is in line with an earlier study that demonstrated a gender effect on tinnitus-related handicap [8]. Moreover, female patients with the same TQ scores like male patients displayed higher Beck Depression Inventory scores and differed in their oscillatory brain activity in the orbitofrontal cortex [36]. The gender influence on the relationship between TQ scores and emotional aspects reflects probably gender differences in emotional regulation [37] and should be considered in further research.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in line with an earlier study that demonstrated a gender effect on tinnitus-related handicap [8]. Moreover, female patients with the same TQ scores like male patients displayed higher Beck Depression Inventory scores and differed in their oscillatory brain activity in the orbitofrontal cortex [36]. The gender influence on the relationship between TQ scores and emotional aspects reflects probably gender differences in emotional regulation [37] and should be considered in further research.…”
Section: Discussionsupporting
confidence: 90%
“…differences in coping with stress demonstrating that repeated exposure to stress causes women to be more vulnerable than men 32 , hence would mean that women assess their tinnitus related comorbidities more intensively than men. To buttress this, Vanneste et al 33 using continuous scalp electroencephalographic (EEG) recordings and low-resolution electromyographic tomography (sLORETA) demonstrated differences in the activity of the prefrontal cortex between males and females in response to stress. They reported higher depression scores in women but did not find gender differences in tinnitus distress and tinnitus intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Since the dlPFC is involved in the regulation of emotions (Fregni et al, 2006;Ochsner et al, 2012), it is also probably influenced by emotional states. On the one hand, the dlPFC, with the ACC, the anterior insula and the amygdala, is part of the distress network activated during auditory stimulation in tinnitus patients (Vanneste et al, 2010b;Vanneste, et al, 2012;De Ridder et al, 2013). On the other hand, the dlPFC is connected to parts of the limbic system, such as the ventromedial prefrontal cortex (vmPFC), which are altered in tinnitus (Mülhau et al, 2006;Leaver et al, 2011;Seydell-Greenwald et al, 2012).…”
Section: Altered Top-down Cognitive Control In Tinnitusmentioning
confidence: 99%